Starch isolation from chestnut and acorn flours through alkaline and enzymatic methods - Correia, Paula Reis; Beirão-da-Costa, Maria Luísa (Food and Bioproducts Processing, 2012)
Two different procedures were used to isolate chestnut (Castanea sativa Mill.) and acorn (Quercus suber) starch. Starch was extracted from the ﬂour of these dried fruits by: (i) low shear at alkaline pH and successively using three sieves (A3S) at different centrifugation conditions (velocity and time) and (ii) enzymatic treatment at low shear (ENZ) at a different amount/digestion time of protease. In both cases a Central Composite Rotatable Design (CCRD) was used as an experimental design. Results were treated through the Response Surface Methodology (RSM). Based on maximum yield values and the degree of purity, the best modiﬁed conditions encountered were applied in a new trial and mass balance was established for both isolation procedures. The best centrifugation conditions encountered for the A3S isolation method were 800 × g during 15min, and for the ENZ method 900 units of protease despite the incubation time, for the same centrifugation terms. The yields reached with these experimental conditions for the A3S and ENZ methods were 83.9% and 79.9% for chestnut and 88.5% and 86.9% for acorn, respectively. Isolated starches shown to be higher in purity, presented values of 98.3% and 96.3% for chestnut and 98.1% and 97.6% for acorn, respectively for the A3S and ENZ methods
The following values have no corresponding Zotero field: publisher: Institution of Chemical Engineers
Keywords: acorn; chestnut; composition; isolation method; starch; yield